Synopsis of Papers Published in the Nigerian Dental Journal: 2007 - 2021 - Olufemi Ogundipe; Kayode Ibitoye (Nigerian Dental Association, 2023)
Using quantitative methods to analyze various aspects of written scientific documents helps to monitor growth of literature and patterns of research. This paper examines the articles published in the Nigerian Dental Journal (NDJ) from 2007 to 2021 for geographical distribution, pattern of study design analysis and topic analysis. Through the review we were able to provide a broad aspect of the types of research published in the Nigerian Dental Journal. Within Nigeria, the contribution from Lagos is the highest while majority of contributions from outside Nigeria were from India. In total 183 articles were published, out of which 103 (56.3%) were full-length articles. The remaining papers included short communications and technical notes. Only one article provided qualitative data, and there were no laboratory-based research highlighting a need to foster further research in this area.